Culture-Independent Species Typing of Neotropical Leishmania for Clinical Validation of a PCR-Based Assay Targeting Heat Shock Protein 70 Genes - Garcia, Lineth (American Society for Microbiology, 2004)
PCR-restriction fragment length polymorphism analysis of heat shock protein 70 genes discriminates most neotropical Leishmania species, as well as Trypanosoma cruzi. The assay, combined with capillary electrophoresis in a microchip device, may be applied directly on clinical samples with a high sensitivity, hence supporting clinical and epidemiological monitoring of leishmaniasis.